Efektifitas Perilaku Kerja Dan Tujuan Kerja Pegawai Terhadap Prestasi Kerja Dosen PNS Di Universitas Mulawarman. - Haeruddian, Haeruddin (BEduManagers Journal : Borneo Educational Management and Research Journal, 2021)
This study aims to analyze the effect of work behavior, teaching work goals, research and service on work performance, and analyze the effect of work behavior on teaching work goals, research and community service. The research method used was a research method combination of explanatory sequential design models. The first phase was conducted using quantitative method. The quantitative data were obtained from 96 lecturers of civil servants at Mulawarman University using a proportional stratified cluster random sampling technique. Data was collected by documentation based on the value of the employee work goals in 2020 which was then analyzed using statistical path analysis. Subsequently, the second phase was carried out using the qualitative method by collecting data through interviews, participant observation and documentation related to work behavior, teaching work goals, research, community service, and job performance of civil servants lecturers at Mulawarman University. The results revealed that 1) there was an influence of behavior, teaching work goals, research and community service together based on quantitative and qualitative analysis, 2) there was an influence of behavior on teaching work goals, research, community service and work performance based on quantitative analysis and qualitative. 3) Based on qualitative data, the leadership style also affected the work performance of lecturers of civil servants at Mulawarman University.